MODEL KEPUTUSAN FUZZY SIMPLE ADDICTIVE WEIGHTING DALAM PEMILIHAN BARANG ELEKTRONIK DI ILTIZAM LHOKSEUMAWE - Muhammad Sadli (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2016)
Docking electronic devices with information technology has been growing very rapidly both with notebook brand, price and specifications of various kinds. Notebook particular laptop has been progressing quite rapidly at this time. Both in terms of hardware, software, and design and specifications offered. This can be demonstrated by the high sales results Notebook in stores Lhokseumawe. Consumers today are not motivated by only one kind of note book in circulation, but can choose more than one in choosing and have the electronic devices. Based on the number of products presented to consumers, ranging from the brand, the hardware specifications, the types of notebooks, and functional from the notebook, consumers are confused when assigning a laptop to be purchased. This shows that when buying a notebook should be tailored to the needs of consumers. the criteria used is the price, screen, processor, vga, memory and hard drive. Difuzzifikasi value is the price. Process models fuzzification stage is inclusion criterion value, the value fuzzification price and value are not in fuzzifikaasi, the second stage of calculating the value of the normalization matrix, revenue weight value, and the final calculation of the value of the preference. The results of the model simple addictive fuzzy weighting in the selection of electronic goods is the highest value of each consumer in choosing a notebook electronic goods.